Embracing the pteridophyte classification of Ren‐Chang Ching using a generic phylogeny of Chinese ferns and lycophytes. Issue 4 (July 2016) - Liu, Hong‐Mei
Abstract: The phylogenetic relationships of pteridophytes occurring in China were reconstructed using DNA sequences of the three plastid genes, atpA, atpB, and rbcL . The sampling comprised all genera of Chinese pteridophytes—including ferns and lycophytes—with the exception of four small genera. The effort to sample all recorded families and genera in a phylogenetic framework enabled the phylogenetic relationships of all Chinese pteridophytes to be addressed for the first time in a single phylogenetic hypothesis. The results provided strong evidence to support the continuing impact of Ren‐Chang Ching's integrative classification of pteridophytes. Ten out of 11 orders accepted by Ching were consistent with the phylogeny, whereas four new orders were introduced to avoid paraphyletic taxa in the leptosporangiate ferns. Of the 63 families considered by Ching, 36 families were supported by molecular data, 22 of those had the same or nearly the same circumscription, and the remaining 14 families were supported but substantially revised. Twenty‐eight small families were now accepted as synonyms. A consistent pattern was observed at the generic level. Among the 223 genera considered by Ching, 133 genera were recognized by the phylogeny, although some of them were substantially changed in the context of circumscription, and 90 were now accepted as synonyms. Three endemic genera were incorporated here for the first time in DNA‐based phylogenetic analyses, namely Blechnidium, Saxiglossum, and Sinephropteris, which were shown to be nested in Blechnum, Pyrrosia, and Asplenium respectively. This paper tentatively accepts 40 families and 151 genera of ferns and lycophytes occurring in China; the importance of phylodiversity of Chinese pteridophytes is also briefly discussed.